Down Syndrome with Congenital Heart Diseases : Referral to Echo Lab for Screening and Diagnosis (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Down syndrome (Trisomy 21) is associated with Congenital Heart Disease (CHD) in 4050% cases. In Bangladesh, parents of Down syndrome cases are visiting to pediatrician for multiple associated comorbidities (Developmental problems, learning problems, hypothyroidism, recurrent infections etc) along with CHD. Though screening of newborns with Down syndrome for congenital heart diseases is recommended in international guidelines, it is not well recognized among the parents in Bangladesh despite of postnatal counseling in hospital deliveries or during visiting pediatrician. Most of the parents do delayed evaluation by pediatric cardiologists. Though clinical findings along with ECG & Chest xray are tools for diagnosis of congenital heart diseases, Echocardiography is still considered the best noninvasive diagnostic procedure. This study was aimed for detecting congenital heart diseases among down syndrome cases, the age at which cases are referred to echocardiography lab for screening & not the least awareness among parents about association of CHD with Down syndrome.Materials and methods : In Chattogram Maa Shishu-O-General Hospital (CMSOGH) a retrospective observational study on cases of down syndrome visiting Echo lab over 1 year (Jan 2020 to Dec 2020). A total of 25 cases of down syndrome were selected based on Karyotyping report.Results : Among 25 cases, 19(76%) of the patients diagnosed for CHD and still a portion of parents (40%) remains unaware of cardiac problems & its association with down syndrome. A number of 9 cases (36%) were detected at the age below 6 months.Conclusion: A major portion of Down syndrome cases are associated with CHD whereas clinically asymptomatic cases may escape diagnosis in hospital settings. Counseling the parents about its association with CHD & significance of early screening should be a routine practice among physicians.Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 7-10